Recovering Context in Psychiatry: What Contextual Analysis of Service Users' Narratives Can Teach About Recovery Support - van Sambeek, Nienke; Baart, Andries; Franssen, Gaston; van Geelen, Stefan; Scheepers, Floortje (Frontiers in Psychiatry, 2021)
Enhancement of recovery-oriented care in psychiatry requires insight into the personal meaning and context of recovery. The Psychiatry Story Bank is a narrative project, designed to meet this need, by collecting, sharing and studying the narratives of service-users in psychiatry. Our study was aimed at expanding insight into recovery through contextual analysis of these first-person narratives. We analyzed 25 narratives, as collected through research interviews. To capture the storied context on both a personal, interpersonal and ideological level we combined several forms of qualitative analysis. A total of 15 narrative characteristics were mapped and compared. Results: Through comparative analysis we identified four narratives genres in our sample: Lamentation (narratives about social loss), Reconstruction (narratives about the impact of psychosis), Accusation (narratives about injustice in care), and Travelogue (narratives about identity transformation). Each genre provides insight into context-bound difficulties and openings for recovery and recovery-support. A contextual approach to studying recovery offers insights that can help attune recovery support in psychiatry. Important clues for recovery support can be found in people’s narrated core struggle and the associated desire to be recognized in a particular way. Our results also indicate that familiarity with different ways of understanding mental distress, can help people to express and reframe their struggles and desires in a helpful way, thereby facilitating recognition.